(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the reflection of moral values through the famous fairy tale by Jean-Marie Le Prince de Beaumont "Beauty and the Beast". The article examines the main themes of the fairy tale - patience, compassion, high morality - and how each of them is expressed in the fairy tale and shown through the characters. The book also discusses the relationships between male and female characters, the moral decisions and spiritual lessons they teach readers. The behavior of the characters in the fairy tale and the role of educational significance attached to them in the socio-cultural context are also analyzed.